Heat conduction - Hahn, David W., 1964- (Wiley, 2012)
"This book supplies the long awaited revision of the bestseller on heat conduction, replacing some of the coverage of numerical methods with content on micro- and nano-scale heat transfer. Extensive problems, cases, and examples have been thoroughly updated, and a solutions manual is available"--